How mangrove forests adjust to rising sea level. Issue 1 (19th November 2013) - Krauss, Ken W.; McKee, Karen L.; Lovelock, Catherine E.; Cahoon, Donald R.; Saintilan, Neil; Reef, Ruth; Chen, Luzhen
Summary: Mangroves are among the most well described and widely studied wetland communities in the world. The greatest threats to mangrove persistence are deforestation and other anthropogenic disturbances that can compromise habitat stability and resilience to sea‐level rise. To persist, mangrove ecosystems must adjust to rising sea level by building vertically or become submerged. Mangroves may directly or indirectly influence soil accretion processes through the production and accumulation of organic matter, as well as the trapping and retention of mineral sediment. In this review, we provide a general overview of research on mangrove elevation dynamics, emphasizing the role of the vegetation in maintaining soil surface elevations (i.e. position of the soil surface in the vertical plane). We summarize the primary ways in which mangroves may influence sediment accretion and vertical land development, for example, through root contributions to soil volume and upward expansion of the soil surface. We also examine how hydrological, geomorphological and climatic processes may interact with plant processes to influence mangrove capacity to keep pace with rising sea level. We draw on a variety of studies to describe the important, and often under‐appreciated, role that plants play in shaping the trajectory of an ecosystem undergoing change.   Contents     Summary 19 I. Introduction 19 II. Important characteristics of mangrove ecosystems 20 III. Patterns of elevation change in mangroves 20 IV. Biological influences on accretion and elevation change 21 V. Factors affecting root contributions to vertical soil development 26 VI. Some potential climatic and environmental feedbacks 29 VII. Perspectives 30   Acknowledgements 31   References 31